2014
DOI: 10.1038/mi.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

C/EBP homologous protein inhibits tissue repair in response to gut injury and is inversely regulated with chronic inflammation

Abstract: Loss of intestinal epithelial cell (IEC) homeostasis and apoptosis negatively affect intestinal barrier function. Uncontrolled activation of the unfolded protein response (UPR) in IEC contributes to an impaired barrier and is implicated in the pathogenesis of inflammatory bowel diseases. However, the contribution of the UPR target gene C/EBP homologous protein (CHOP), an apoptosis-associated transcription factor, to inflammation-related disease susceptibility remains unclear. Consistent with observations in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Treatment with an anti-TL1A antibody decreases the amount of IFNγ and IL-17A produced and attenuates weight loss, colon shortening, and the histologic inflammation seen in this model of chronic colitis. These findings are corroborated in two other models of T cell-mediated chronic colitis [92, 93]. TL1A’s effect on the production of Th1- and Th17-related cytokines is supported using T cells and macrophages isolated from the intestinal LP and peripheral blood (PB) of patients with CD.…”
Section: Introductionsupporting
confidence: 60%
“…Treatment with an anti-TL1A antibody decreases the amount of IFNγ and IL-17A produced and attenuates weight loss, colon shortening, and the histologic inflammation seen in this model of chronic colitis. These findings are corroborated in two other models of T cell-mediated chronic colitis [92, 93]. TL1A’s effect on the production of Th1- and Th17-related cytokines is supported using T cells and macrophages isolated from the intestinal LP and peripheral blood (PB) of patients with CD.…”
Section: Introductionsupporting
confidence: 60%
“…We expected the UPR-related transcription factor CHOP to be involved, since CHOP has been shown to induce cell cycle arrest43. Recently, we generated epithelial-specific Chop transgenic mice and demonstrated that high levels of CHOP attenuate cell cycle progression leading to delayed epithelial proliferation and wound closure in response to colonic injuries34. Nevertheless, using Chop −/− Hsp60 Δ/ΔIEC mice in this study did not indicate any impact of CHOP-mediated signals on mitochondrial dysfunction-associated loss of proliferation and stemness.…”
Section: Discussionmentioning
confidence: 99%
“…MT-UPR in mammals is rather poorly described, but mechanistic studies in a primate-derived cell line identified the transcription factor CHOP and its cofactor C/EBPβ to induce expression of MT-UPR responsive chaperones like HSP60, its co-chaperone HSP10 and proteases like ATP-dependent caseinolytic peptidase proteolytic subunit homologue (CLPP)313233. By using an epithelial-specific Chop transgenic mouse model, we recently showed delayed epithelial proliferation and intestinal wound healing in response to increased levels of CHOP, suggesting CHOP to affect intestinal homeostasis by attenuating cell cycle progression34.…”
mentioning
confidence: 99%
“…Recent studies 314 have demonstrated that CHOP is associated with the inflammatory re-315 sponse [37,38]; activation of caspase 11-caspase 1 by CHOP stimulates 316 IL-1 and IL-1β productions in the lung exposed to LPS. In this present 317 study we found that that I/R induced inflammatory response, and the 318 increase of inflammatory response was attenuated by CHOP deficiency, 6.…”
mentioning
confidence: 99%